Under the same roof? The Green Belt and Road Initiative and firms' heterogeneous responses - Mingming Jiang; Jianhong Qi; Zhitong Zhang (Journal of Applied Economics, 2022)
Launched in 2017 the Green Belt and Road policy acts as an important upgrade to China's recent core foreign strategy (i.e., the Belt and Road Initiative) and aims to balance the economic development and environmental harmony in countries along the routes. In this paper, we take the implementation of this green policy as a quasi-natural experiment and employ a difference-in-difference method to identify the impact of the policy on Chinese outward direct investment (ODI) firms. We find that the policy has a significant and robust effect on improving the overall performance of ODI firms. Under the same policy roof, however, the seemingly similar impact masks the distinct responses of state-owned and non-state-owned enterprises. Non-state-owned enterprises improve their performance by pursuing green credits and technology upgrades. State-owned enterprises achieve improved performance through better compliance with the green policy and the accompanying government subsidies, in addition to technology upgrades.
Keywords: 330; corporate financing; firms' performance; government subsidy; Green Belt and Road Initiative; state ownership; technological innovation